ORTHODONTIC AND ORTHOPEDIC REHABILITATION OF PATIENTS WITH CLEFT OF UPPER LIP, ALVEOLAR SURGERY, HARD AND SOFT PALATE - O.M. Makarova; M.V. Semenyaka; G.M. Balya; V.D. Kuroyedova (Український стоматологічний альманах, 2018)
The problem of children’s rehabilitation with cleft palate is multi edged and complex. The ultimate goal of rehabilitation measures is to restore the anatomical integrity of the tissues of the hard and soft palate, the function of the articulatory and mastication systems, create conditions for correct speech and maximum aesthetic rehabilitation.